Ancient DNA investigation of the domestication history of pigs in Northeast China. (May 2022) - Wang, Yongdi; Sun, Yang; Royle, Thomas C.A.; Zhang, Xinyu; Zheng, Ying; Tang, Zhuowei; Clark, Lauren T.; Zhao, Xin; Cai, Dawei; Yang, Dongya Y.
Abstract: Archaeological evidence demonstrates that China was one of many early centers of pig domestication. Yet, it remains uncertain whether there was a single center or multiple centers within China. A recent ancient DNA study of archaeological pig remains hypothesized that in addition to the North China Plain, Northeast China may have also been a pig domestication center. In this study, we conducted ancient DNA analysis on 35 pig remains from Wanfabozi (6–2.2 kBP) and Dashanqian (4–2.2 kBP) in order to better understand the regional history of ancient pigs in Northeast China. Analysis of a 279 bp fragment of the mitochondrial D-loop indicates that pigs at these sites, particularly Wanfabozi, exhibit high haplotype diversity relative to sites in the North China Plain. Our analysis also revealed multiple haplotypes at these sites that are unique to Northeast China as well as some haplotypes shared with pigs in the North China Plain. The high genetic diversity and unique haplotypes at these sites likely reflect the use of wild boars, which are still abundant in the region today. Moreover, the presence of haplotypes shared with the North China Plain suggests domestic pigs were not likely independently domesticated in Northeast China but imported from the North China Plain. The results of our study also highlight the difficulties surrounding the identification of wild versus domestic swine using mtDNA alone and addresses the need to incorporate other lines of evidence when assessing the domestications status of archaeological pigs. Highlights: Pigs from Northeast China and earlier pigs from North China share mtDNA haplotypes. Data suggest Northeast China was not an independent center of pig domestication. Extensive haplotype sharing between Chinese domestic pigs and wild boars. Results demonstrate that domestication was a continuous process. To understand domestication, need to integrate DNA and archaeological data.